2021
DOI: 10.3389/fphys.2021.766867
|View full text |Cite
|
Sign up to set email alerts
|

The Design and Evaluation of a Portable Extracorporeal Centrifugal Blood Pump

Abstract: In recent years, blood pumps have become the bridge to heart transplantation for patients with heart failure. Portability and wearability of blood pumps should be considered to ensure patient satisfaction in everyday life. To date, the focus has been on the development of portable and wearable peripheral components, little attention has been paid to the portable and wearable performance of the blood pump itself. This study reported a novel design of a wearable and portable extracorporeal centrifugal blood pump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…In addition, some studies also revealed that for continuous blood pumps, a steady simulation method is feasible. 6,43 Second, it is important to consider the number of particles. Under normal conditions, the platelet density in human blood is $250 Â 106 platelets/ml, which is much higher than the number of platelets released by numerical simulations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some studies also revealed that for continuous blood pumps, a steady simulation method is feasible. 6,43 Second, it is important to consider the number of particles. Under normal conditions, the platelet density in human blood is $250 Â 106 platelets/ml, which is much higher than the number of platelets released by numerical simulations.…”
Section: Discussionmentioning
confidence: 99%
“…The convective terms were solved in high-resolution form and the SST k-ω turbulence model 2,41 was employed for stabilization simulations. 6,43 The frozen rotor interface was placed downstream of the trailing edge of the blades as the interface between the rotating region (impeller, clearances, and secondary flow passage) and the stagnant regions (inlet pipe and volute). To avoid the effect of insufficient development flow on the simulation results, both the inlet and outlet of blood pump were extended about 10 times of pipe diameter.…”
Section: Cfd Methodsmentioning
confidence: 99%
“…The Reynolds‐averaged Navier–Stokes (RANS) equations were solved using the commercial software Ansys CFX (ANSYS Inc., Canonsburg, PA, USA), which employs a finite‐volume method based on discretization of the governing equations. The convective terms were solved in high‐resolution form and the SST k‐ω turbulence model 20,64 was employed for stabilization simulations 21,66 . The frozen rotor interface was placed downstream of the trailing edge of the blades as the interface between the rotating region (impeller, clearances, and secondary flow passage) and the stagnant region (inlet pipe and volute).…”
Section: Methodsmentioning
confidence: 99%
“…The convective terms were solved in high-resolution form and the SST k-ω turbulence model 20,64 was employed for stabilization simulations. 21,66 The frozen rotor interface was placed downstream of the trailing edge of the blades as the interface between the rotating region (impeller, clearances, and secondary flow passage) and the stagnant region (inlet pipe and volute). A mass flow rate of 0.088 kg/s (obtained from the volume flow rate of 5 L/min) boundary condition was set at the inlet and static pressure (0 mm Hg) boundary condition was set at the outlet.…”
Section: Cfd Methodsmentioning
confidence: 99%
“…Reynolds-averaged Navier–Stokes (RANS) equations were solved using the commercial software Ansys CFX (ANSYS Inc., Canonsburg, PA, USA), which employs a finite-volume method, based on discretization of governing equations. The convective terms were solved in high-resolution form, and the SST k-ω turbulence model [ 18 , 20 ] was employed for stabilization simulations [ 21 , 22 ]. In addition, a normal artery without an intravascular pump (no-pump case) was analyzed, to calculate the normal/base levels, as the control group for evaluating the effect of adding an intravascular pump, in which the blood was considered as laminar flow.…”
Section: Methodsmentioning
confidence: 99%